Dari Gujarat ke Nusantara: Dinamika Islamisasi dan Pembentukan Identitas Muslim Asia Tenggara - Yohanis Kristianus Tampani; Sandro Christianto Asa; Selviana Tati Hale; Virmigaldis Selvia Hoar; Yance Y. K Bien; Felixanus Teti; Augusta De Jesus Magalhaes (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the role of Gujarat, India, as a major hub in the dynamics of the Islamization of the Indonesian Archipelago (Nusantara) and its impact on the formation of a distinctive Southeast Asian Muslim identity. This research employs a library research method by examining various primary and secondary sources, including historical manuscripts, travel accounts, archaeological findings, and relevant scholarly books and journal articles. The findings indicate that the arrival and spread of Islam in the Nusantara around the thirteenth century were strongly influenced by Muslim traders from Gujarat, who functioned not only as economic agents but also as carriers of religious and cultural values. The process of Islamization occurred relatively peacefully through trade networks, intermarriage, Islamic education, and political alliances with local rulers. The dominance of Sufistic teachings, which were adaptive and accommodative to local cultural traditions, facilitated a process of cultural inculturation that enabled Islam to be accepted without significant social conflict. This interaction produced a moderate and syncretic form of Islam, reflected in religious practices, local traditions, and Islamic architectural forms across the region. The study concludes that the Islamization of the Nusantara was a continuous process of cultural dialogue that shaped a tolerant, contextual, and harmonious Muslim identity in Southeast Asia, distinguishing it from Middle Eastern Islamic traditions.